Effects of polymer doping on dielectric and electro‐optical parameters of nematic liquid crystal. Issue 2 (3rd March 2014) - Pandey, Shivani; Gupta, Swadesh Kumar; Singh, Dharmendra Pratap; Vimal, Tripti; Tripathi, Pankaj Kumar; Srivastava, Atul; Manohar, Rajiv
<x xml:space="preserve">Abstract</x> Poly(isobutyl methacrylate) (PiBMA) polymer doped in pure p‐Ethoxybenzylidene p‐Heptylaniline (EBHA) mesomaterial has been investigated in the present study. The dielectric and electro‐optical parameters of EBHA having nematic phase were altered due to the addition of polymer in different concentration. The strong dopant concentration dependent nature of negative dielectric anisotropy and conductivity are the interesting results of the present polymer doped nematic liquid crystal (NLC) system. The present composite shows its useful application in low charge consumable devices due to the easy charge transportation phenomenon. The investigated polymer doped‐NLC system exhibiting increased negative dielectric anisotropy and high conductivity may prove to be advantageous for video applications in vertically aligned cells. POLYM. ENG. SCI., 55:414–420, 2015. © 2014 Society of Plastics Engineers